Inducing food insecurity: financialisation and development in the post-2015 era. Issue 5 (3rd May 2016) - Brooks, Sally
Abstract: The G7 'New Alliance for Food Security and Nutrition' follows an established approach of 'connecting smallholder farmers to markets', while extending the role and influence of corporate agri-business in new ways. This paper explores the implications of the 'New Alliance' model's incorporation into the Sustainable Development Goals framework for smallholder producers already facing greater uncertainty in financialised agri-food chains, and in light of a consensus around the primacy of private finance in the post-2015 era. The question for alternative food and development movements is how to confront the 'value chain challenge' in an increasingly financialised global agri-food system.